2008
DOI: 10.1080/00223131.2008.10875971
|View full text |Cite
|
Sign up to set email alerts
|

Site- and State-Selective Dissociation of Core-Excited Organic Molecules: Deuterium-Labeled Methyl Acetate

Abstract: Site-and state-selective dissociation of methyl acetate induced by core level excitation has been studied in the oxygen K-edge region using time-of-flight fragment-mass spectroscopy. O1s core (C=O/OMe) to valence (C{OMe ) excitation bands in the total-ion-yields of methyl acetate were assigned based on the comparison with those of other esters and band-deconvolution analysis. Product branching ratios of CD 3 þ and CDO þ cations from deuterium-labeled methyl-d 3 acetate (CH 3 C(O)OCD 3 ) showed that site-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For example, Okada and co-workers found the branching ratios of specific dissociation from 2-, 3-, and 4-pyridine to be only 1.2–1.9% . Kawasaki et al found the branching ratio of product CD 3 + to increase from 5.9% (excited at 535.1 eV) to 12.8% (excited at 531.9 eV) from CH 3 COOCD 3 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Okada and co-workers found the branching ratios of specific dissociation from 2-, 3-, and 4-pyridine to be only 1.2–1.9% . Kawasaki et al found the branching ratio of product CD 3 + to increase from 5.9% (excited at 535.1 eV) to 12.8% (excited at 531.9 eV) from CH 3 COOCD 3 …”
Section: Results and Discussionmentioning
confidence: 99%
“…50 Kawasaki et al found the branching ratio of product CD 3 + to increase from 5.9% (excited at 535.1 eV) to 12.8% (excited at 531.9 eV) from CH 3 COOCD 3 . 51 Although the K-edge spectra of amino acids and small peptides have been studied extensively, the dissociation pathways of peptides after core excitation has not been thoroughly investigated. 49,52 We demonstrate in the current study that the branching ratios after breakage of the peptide bond can be as high as 0.56−0.71.…”
Section: ■ Theoretical Calculationsmentioning
confidence: 99%
“…Closely related techniques were later extended to a range of molecular targets, starting with halocarbons and zero-valent metal complexes by several teams [3][4][5][6][7][8]. In all these later works with the exception of that of de Brito et al [6,7] on ozone, site-specific excitations were created at atoms of different elements in the target molecules; detection of a single Auger electron then identifies the atom and also determines the energy deposited in the final singly-ionized state.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for 2-, 3-, and 4-methylpyridine, Okada and coworkers found the branching ratios of specific dissociation to be only 1.2−1.9%. 67 For the specific bond dissociation of CH 3 COOCD 3 at the O K-edge, Kawasaki et al 68 found the branching ratio of the product CD 3 + to increase from 5.9% (with excitation at 535.1 eV) to 12.8% (with excitation at 531.9 eV). For the products of methanol following core excitation at the carbon and oxygen K-edges, Stolte and co-workers found that the anionic product OH − was produced at only the C Kedge while O 2+ was observed only at the O K-edge.…”
Section: ■ Discussionmentioning
confidence: 99%